1992
DOI: 10.3109/02770909209048937
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Theophylline Concentrations and Airway Function in Asthmatic Children Receiving Standard and Modified RTC Therapy

Abstract: The effects of three different dosage schedules for sustained-release theophylline (Theolong) were investigated in children with asthma. With regimen II (unequal doses at 0800 h and 2000 h), the maximum plasma theophylline concentration following the evening dose was significantly higher than that following the morning dose, and also was larger than that following the evening dose with regimen I (equal doses at 0800 and 2000 h). With regimen III (equal doses at 0600 h and 2100 h), the mean theophylline concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Recently, it has been demonstrated that low‐dose theophylline improves asthma symptom control more than a leukotriene antagonist, montelukast, and is a safe and less expensive alternative asthma treatment for the patients not using ICS [15]. Although theophylline is currently less preferred than leukotriene antagonist or a long‐acting β 2 ‐agonist, long‐term administration of theophylline [38] (round‐the‐clock therapy; RTC) should be reconsidered for the management of bronchial asthma due to its anti‐inflammatory effects on DC proliferation and survival for an add‐on therapy with ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that low‐dose theophylline improves asthma symptom control more than a leukotriene antagonist, montelukast, and is a safe and less expensive alternative asthma treatment for the patients not using ICS [15]. Although theophylline is currently less preferred than leukotriene antagonist or a long‐acting β 2 ‐agonist, long‐term administration of theophylline [38] (round‐the‐clock therapy; RTC) should be reconsidered for the management of bronchial asthma due to its anti‐inflammatory effects on DC proliferation and survival for an add‐on therapy with ICS.…”
Section: Discussionmentioning
confidence: 99%